Gut dysbacteriosis attenuates resistance to Mycobacterium bovis infection by decreasing cyclooxygenase 2 to inhibit endoplasmic reticulum stress - Haoran Wang; Jiao Yao; Yulan Chen; Yuanzhi Wang; Yiduo Liu; Yi Liao; Zhengmin Liang; Yu hui Dong; Mengjin Qu; Xin Ge; Xiangmei Zhou (Emerging Microbes and Infections, 2022)
The role of gut microbiota has been described as an important influencer of the immune system. Gut-lung axis is critical in the prevention of mycobacterium infection, but the specific mechanism, by which dysbiosis affects tuberculosis, has not been reported. In this study, we attempted to provide more information on how the gut-lung axis contributes to Mycobacterium bovis (M. bovis) infection. Mice are pre-treated with broad-spectrum antibiotics cocktail (Abx) to induce gut dysbiosis. Interestingly, dysbiosis of microbes showed a significant increase in the bacterial burden in the lungs and inhibited the level of COX-2. After faecal transplantation, cyclooxygenase 2 (COX-2) expression was restored and the inflammatory lesion in the lungs was reduced. Further research found that the deficiency of COX-2 inhibited endoplasmic reticulum stress (ER stress). This mechanism was completed by COX-2 interaction with BIP. Moreover, we found a positive feedback mechanism by which blocking ER stress could reduce COX-2 levels by the NF-κB pathway. Taken together, we reveal for the first time gut dysbacteriosis exacerbates M. bovis disease by limiting the COX-2/ER stress pathway. The finding strengthens the foundation of gut microbiota-targeted therapy for tuberculosis treatment.